(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe several clinical and bacteriological characteristics in patients with chronic rhinosinusitis (CRS). Patients and Methods: A prospective, case-by-case descriptive study was conducted on 96 patients diagnosed with CRS at the Military Hospital 103 from May 2024 to March 2025. Results: Nasal obstruction and rhinorrhea were the most common symptoms, observed in 100% of cases; facial pain or pressure was present in 68.8%; mucosal edema in 91.7%, purulent discharge in the middle meatus in 89.6%, and in the sphenoethmoidal recess in 69.8%. Of the 96 specimens, 71.9% yielded positive bacterial cultures; in all cases with purulent rhinorrhea (white/yellow/green discharge), bacterial cultures were positive. Staphylococcus aureus and Streptococcus pneumoniae were the most frequently isolated bacteria, accounting for 60.9% and 18.8% respectively. Less common isolates included Haemophilus influenzae (7.2%), then Moraxella catarrhalis, Pseudomonas aeruginosa, and Klebsiella pneumoniae (each 4.3%). Conclusions: The primary clinical symptoms were nasal discharge and obstruction (100%). The main endoscopic findings were mucosal edema (91.7%) and purulent secretions in the middle meatus and sphenoethmoidal recess. The most common bacterial pathogens isolated from patients with CRS were Staphylococcus aureus (60.9%) and Streptococcus pneumoniae (18.8%).